Clients' Role in Attainment of Sustainability in Housing: The Case of Singapore and Lessons for Developing Countries - George Ofori (Journal of Construction in Developing Countries, 2007)
The adverse effect of the construction of houses and other buildings and infrastructure on the earth's environment has been highlighted in the literature. Proposals on how the planning, designing, constructing and maintaining of residential units can be undertaken under the framework of "sustainable development" (or "sustainable housing") have also been made. Housing units built in this way would have less environmental impact. Housing is a basic human need, and most governments are committed to ensuring that all their citizens have decent standards of housing. There are currently gaps between needs and provisions in almost all countries. Large volumes of resources will be required if these gaps are to be filled. There will also be other environmental impacts from such levels of activity. This paper discusses recent developments in sustainable housing. It focuses on the role of the client. It reviews the current situation with respect to sustainable housing in Singapore, putting it in the context of the national policies and programmes for sustainable development. It discusses the practices of the larger clients of housing developments in Singapore. Possible lessons for other countries are inferred. It is suggested that further education of the client is necessary. Moreover, there is the potential for end purchasers to be similarly educated, in order to form them as a market force for change.